The Impact of Serum Ghrelin on Body Mass Index in Children with Type1 Diabetes Mellitus - Ayash, Safa A.; Elyaseen, Hedef Dh.; Alzubaidi, Munib A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Insulin produced by pancreatic β cells ceases in people with type1 diabetes mellitus, an endocrine disease caused by autoimmune damage. It can cause weight loss. Energy balance controls the secretion of ghrelin, a peptide hormone made by entering endocrine cells found in the oxyntic glands of the stomach fundus. Objectives: This study aimed to investigate the relationship between serum ghrelin and body mass index in newly diagnosed children with type 1 diabetes mellitus.Methods: The study involved 120 pediatric participants aged 2-14 years conducted from February to May 2024. They were divided into four groups: group 1 contains 40 lean patients with type 1 diabetes mellitus and a body mass index ≥85 percentile, group 2: 40 underweight patients with type1 diabetes mellitus and a BMI ≥5 percentile, group 3: 22 healthy lean controls with a body mass index